2011
DOI: 10.1097/jom.0b013e318221c6fe
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Risk of LVH and ECG Abnormalities in US Firefighters

Abstract: Obese firefighters appear to have a higher risk of LVH and ECG abnormalities than normal-weight individuals. Our findings need further evaluation and may have important implications for occupational health policies and periodic medical evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…This can be explained in large by the high prevalence of obesity that was documented among those noncardiac traumatic controls, while in addition our results suggested the prevalence of cardiac enlargement to be steadily increasing as a function of BMI. Our findings are consistent with the literature, which finds obesity to be a significant risk factor for LVH and increased cardiac mass [1,14]. Furthermore, one could hypothesize that traumatic fatalities occur more frequently in obese firefighters as they could be more inclined to be physically trapped during a fire secondary to their body size and relative physical immobility [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This can be explained in large by the high prevalence of obesity that was documented among those noncardiac traumatic controls, while in addition our results suggested the prevalence of cardiac enlargement to be steadily increasing as a function of BMI. Our findings are consistent with the literature, which finds obesity to be a significant risk factor for LVH and increased cardiac mass [1,14]. Furthermore, one could hypothesize that traumatic fatalities occur more frequently in obese firefighters as they could be more inclined to be physically trapped during a fire secondary to their body size and relative physical immobility [21].…”
Section: Discussionsupporting
confidence: 91%
“…Increasingly, evidence from the general population points a major role of left ventricular hypertrophy (LVH)/cardiomegaly in the risk of sudden cardiac death (SCD), either alone or together with co-morbid Coronary Heart Disease (CHD) [11][12][13]. Moreover, evidence from studies based on autopsy reports from formerly active career firefighters, indicates that LVH/cardiomegaly is common among US firefighters and plays a major role in on-duty CVD events and SCD risk in the fire service [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the studies, which find obesity to be a risk factor for LV hypertrophy and increased cardiac mass. 9 , 10 In addition, given that obesity is associated with cardiovascular disease (CVD) risk factor clustering, 11 , 12 it probably explains why other factors such as blood pressure and obstructive sleep apnea risk were weaker predictors because of their association with LV mass may be closely linked to their association or co-morbidity with obesity. 13 Given our previous findings that obesity-associated sudden cardiac death (SCD) among younger firefighters was largely driven by an increased cardiac mass in SCD victims compared with controls, 14 our results reinforce that decreasing obesity in the fire service will lower the risk of LV hypertrophy and on-duty CVD events, particularly SCD.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective investigation on the association between BMI and the incidence of electrocardiographic alterations in a large group of fire-fighters found that obese individuals were about two times more likely to develop LVH during a mean follow-up period of 4 years than their normalweight counterparts [12]. Among the 3922 healthy participants of the Framingham Heart Study, BMI was strongly related with left-ventricular mass, left-ventricular wall thickness and left-ventricular internal dimensions after adjusting for age and blood pressure (BP) [13].…”
Section: Introductionmentioning
confidence: 99%